Raising the profile of woodfuels in the forest landscape restoration agenda - Harvey, C.A.; Guariguata, Manuel R. (Wiley, 2021)
Forest landscape restoration (FLR) is being promoted as a means of tackling global challenges including land degradation, climate change, biodiversity conservation and sustainable development. However, as the FLR agenda gains momentum, it is critical that FLR initiatives pay sufficient attention in promoting the sustainable management of woodfuels, so far overlooked. In many regions, woodfuels (firewood and charcoal) are the main energy source for households and play a pivotal role in local economies; yet they are also associated with environmental degradation and adverse health outcomes. Here we examine the reasons why it is important to raise the profile of woodfuels within the FLR agenda and highlight the enabling conditions needed to promote sustainable management of woodfuels. In landscapes where woodfuel use is prevalent, FLR initiatives should consider enhancing wood fuel supply by growing trees, promoting fuel‐efficient cookstoves and kilns, and shifting pressure from natural forests and woodlands to planted trees. We argue that if wood fuel issues are considered in the design, implementation and monitoring of FLR initiatives and are supported by appropriate policies, resources and technical capacity, this will greatly enhance the sustainability and success of FLR initiatives.